Meet me in another life : a novel - Silvey, Catriona (William Morrow, an imprint of HarperCollins Publishers, 2021)
Thora and Santi are strangers in a foreign city when a chance encounter brings them together and intertwines their fates. Thora thinks she's finally found a kindred spirit with the same intelligence, offbeat humor, and desire to look up instead of straight ahead. But days later, Santi is cruelly taken from her in an accident. But this is just one of the many connections they share. Like two satellites trapped in orbit around each other, Thora and Santi meet again: as a nurse and dying patient; a teacher and prodigy student; a cynic and a believer. In numerous lives they become friends, colleagues, lovers, and enemies, but how and why? When ominous patterns begin to emerge and the lines between worlds blur, Thora and Santi come to a shocking revelation, they must discover the truth of their strange attachment before their many lives come to a final end.